Barriers and facilitators in antenatal settings to screening and referral of pregnant women who use alcohol or other drugs: A qualitative study of midwives' experience. (February 2020) - Oni, Helen Tosin; Buultjens, Melissa; blandthorn, Julie; Davis, Deborah; Abdel-latif, Mohamed; Islam, M. Mofizul
Abstract: Background: Screening pregnant women for substance use is highly recommended in antenatal care settings. Although midwives provide routine screening for substance use and referral for treatment in pregnancy, little is known about the barriers and facilitators they experience. Aim: The study explored barriers and facilitators experienced by midwives in antenatal settings to screening and referral of pregnant women who use alcohol or other drugs. Design/setting: A semi-structured interview was adopted to explore barriers and facilitators experienced by midwives in screening and referring pregnant women for alcohol or other drugs specialised services. Eighteen midwives were recruited from urban, regional and rural antenatal settings in Victoria. Interviews were tape recorded and transcribed verbatim. Themes were generated by thematic analysis, the process of identifying patterns within the data. Findings: Of the seven themes identified under barriers, five could be categorised as "institution and provider-related", namely: (i) lack of validated screening tool, (ii) inadequate support and training, (iii) discomfort in screening, (iv) lack of multidisciplinary team and specialised treatment in regional and rural areas, and (v) workload and limited consultation time . Conversely, two themes could be classified as 'client-related', namely (i) non- or partial-disclosure of substance use, and (ii) reluctance and non-adherence to referrals. All five themes under facilitators were "institution and provider-related." They are (i) a woman-centred philosophy of care, (ii) evidence of harms from substance use on neonates, (iii) experience and training, (iv) continuity of care, and (v) availability of multidisciplinary team and funding . Key conclusions and implications for practice: To the best of our knowledge, this is the first study of its kind conducted in Victoria. This study not only adds to the limited body of knowledge on barriers experienced by midwives but also identifies facilitators in antenatal settings that promote screening and referral of pregnant women who use substance. Most of the barriers and facilitators are interrelated. Despite midwives' willingness to screen all pregnant women for substance use and provision of referral, they often felt limited in their capacity. Availability and accessibility to validated screening tool(s), in addition to regular, ongoing training for all midwives to maintain clinical competence and provide effective communication are imperative. Availability of a multidisciplinary team, funds and specialised care facilities such as detoxification and mental health services, especially in regional and rural areas, are necessary to effectively support at-risk pregnant women.